Different patterns of pfcrt and pfmdr1 polymorphism in Plasmodium falciparum isolates from Tehama region, Yemen - Atroosh, Wahib M.; Al-Mekhlafi, Hesham Mahyoub; Al-Jasari, Adel; Sady, Hany; Dawaki, Salwa S.; Elyana, Fatin N.; Al-Areeqi, Mona A.; Nasr, Nabil A.; Abdulsalam, Awatif Mohamed; Subramaniam, Lahvanya R.; Azzani, Meram; Ithoi, Init; et al. (PeerJ, 2016)
Introduction. Despite the efforts of the malaria control programme, malaria morbidity is still a common health problem in Yemen, with 60% of the population at risk. Plasmodium falciparum is responsible for 99% of malaria cases. The emergence in Yemen of parasite resistance to chloroquine (CQ) prompted the adoption of artemisinin combination therapy (ACT) in 2009, which involves the use of artesunate plus sulphadoxine-pyrimethamine (AS + SP). However, CQ was retained as the drug of choice for vivax malaria. To assess the impact of the change in the malaria treatment policy five years after its introduction, the present study investigated the mutations in the CQ resistance transporter (pfcrt ) and multidrug resistance 1 (pfmdr1) genes. Method. A molecular investigation of 10 codons of pfcrt (72-76, 220, 271, 326, 356, and 371) and five codons of pfmdr1 (86, 184, 1034, 1042, and 1246) was conducted on P. falciparum isolates from districts with the highest malaria endemicity in the Hodeidah and Al-Mahwit governorates in Tehama region, Yemen. A total of 86 positive cases of falciparum monoinfection were investigated for the presence of mutations related to CQ and other antimalarials using a PCR-RFLP assay. Results. There was a wide prevalence of pfcrt gene mutations with the pfcrt 76T CQ resistance marker being predominant (97.7%). The prevalence of other pfcrt mutations varied from high (75E: 88%) to moderate (74I: 79.1%, 220S: 69.8%, 271E and 371I: 53.5%) or low (326S: 36%, 72S: 10.5%). Mutated pfcrt 72-76 amino acids haplotypes were highly prevalent (98.8%). Among these, the CVIET classic, old-world African/Southeast Asian haplotype was the most predominant, and was mostly found in the isolates from the Khamis Bani Saad district of Al-Mahwit (93.1%) and the AdDahi district of Hodeidah (88.9%). However, it was only found in 26.3% of the isolates from the Bajil district of Hodeidah. Surprisingly, the SVMNT new-world South American haplotype was exclusively detected in 9.3% of the isolates from the Bajil district of Hodeidah. Mutations at Y184F of pfmdr1 were found in all isolates (100%) from all districts. The mutation for codons 1034C and 86Y were found only in the isolates from the AdDahi and Khamis Bani Saad districts. Overall, the AdDahi and Khamis Bani Saad districts were similar in terms of carrying most of the mutations in the pfcrt and pfmdr1 genes, while there was a lower prevalence of mutation in the isolates from the Bajil district. Conclusion. The high prevalence of mutations in pfcrt 5 years after the official cessation of CQ use against P. falciparum suggests that there is sustained CQ pressure on P. falciparum isolates in the study area. Moreover, the low prevalence of mutations in the pfmdr1 gene could be a good indicator of the high susceptibility of P. falciparum isolates to antimalarials other than CQ. A new strategy to ensure the complete nationwide withdrawal of CQ from the private drug market is recommended.